AGRO-INDUSTRIAL ORGANIC RESIDUE INFLUENCE THE PRODUCTION OF HUMUS AND MULTIPLICATION OF EARTHWORMS - Camila Soares Santos, Mayara; Santos, Cleberton Correia; de Sá Motta, Ivo (Revista Brasileira de Engenharia de Biossistemas, 2021)
Among the techniques used in the use of agro-industrial residues, vermicomposting, that is, the use of earthworms in the degradation of these wastes through the digestive tract, transforming in humus. The earthworms Eudrilus eugeniae ("gigante Africana") is widely used in this process of biotransformation and stabilization of these materials. Thus, the aim of this work was to know the feasibility of the use of agro-industrial residues in the production of humus and multiplication of earthworm. The treatments were constituted by different ratios of ruminal content (RC) and sugarcane bagasse (SB), being: T1) 100% RC; T2) 87.5% RC + 12.5% SB; T3) 75% RC + 25% SB; T4) 62.5% RC + 37.5% SB; T5) 50% RC + 50% SB. Realizamos a inoculação de Eudrilus eugeniae e após 78 dias, a minhoca e a massa de húmus foram quantificadas. A combinação de 75% de conteúdo ruminal + 25% de bagaço de cana proporciona melhores condições para a multiplicação de Eudrilus eugeniae . Em relação à produção de húmus, 100% do conteúdo ruminal permite maior produção do mesmo e esta diminui com a adição de bagaço de cana.